Afectual Management: Confidence Build-Up, Technological Barriers and Compassionate Solidarities - Agung Pramana; Mantilie; Yohanes Yappo; Yesyurun Munthe (Eastasouth Institute, 2023)
The background of this research is to find and examine the symmetrical and paradoxical experiences when meeting and being present, melting, being sucked in and separated in the midst of the dynamic and timeless period. Learning and learning outcomes as downstream products of learners often eliminate the process as an essential part of the experience and even become different processes of handling, mentoring and regulation even though ostensibly in the name of context and sustainability but eliminating the voices of learners. The purpose of this research is to explore the extent of experience capable of self-reflection and then the research subjects are capable of weighing, deciding and empowering themselves for their efforts or conditions of shock that bring an atmosphere of amazement. This research is based on qualitative research with data search techniques through an interview process with three research subjects who hold the status of students in the city of Palangka Raya. The results showed that filling learning time during the pandemic and post-pandemic signaled that responsibility, independent learning, questioning competence, self-building and recovery were buildings that transformed as solidarity across psychologically vulnerable subjects amid the uncertainty of time and life.